2002
DOI: 10.1034/j.1399-6576.2002.t01-1-460315.x
|View full text |Cite
|
Sign up to set email alerts
|

Ropivacaine 2 mg/mL vs. bupivacaine 1.25 mg/mL with sufentanil using patient‐controlled epidural analgesia in labour

Abstract: The results support the findings of previously published studies postulating ropivacaine to be 40-50% less potent for labour epidural analgesia compared to bupivacaine. However, we observed an increased frequency of instrumental deliveries with ropivacaine. To evaluate the clinical relevance of these findings, further investigations are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Ten studies 11,12,[15][16][17][18][19][20][21][22] were finally selected by following inclusion and exclusion criteria. The study screening and selection process is depicted in Figure 1 and the characteristics of the included studies including patients' demographic and obstetric data, and concentration of anesthetics used in each study is presented in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ten studies 11,12,[15][16][17][18][19][20][21][22] were finally selected by following inclusion and exclusion criteria. The study screening and selection process is depicted in Figure 1 and the characteristics of the included studies including patients' demographic and obstetric data, and concentration of anesthetics used in each study is presented in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas Buyse et al 15 have shown that the dose sparing effect of sufentanil is greater for bupivacaine (up to 90%) than for ropivacaine or levobupivacaine (up to 78%), van de Velde et al 11 in a dose-response study noticed that in combination with sufentanil, racemic bupivacaine is more potent than ropivacaine (1.4 times) and levobupivacaine (1.5 times) with ED95 of ropivacaine and levobupivacaine of 4.8 mg (95% CI, 4.0-6.7) and 5.0 mg (95% CI, 4.1-7.0), respectively. Wang et al 12 have calculated the EC50 and EC95 by using probit regression as: 0.044% (0.031%-0.056%) and 0.177% (0.138%-0.261%) for bupivacaine, 0.053% (0.039%-0.066%) (a) Clement et al 17 Fischer et al 18 Gautier et al 19 Gogarten et al 20 Hoffman-kiefer et al 21 Van de Velde et al 11 17 Fischer et al 18 Gautier et al 19 Gogarten et al 20 Hoffman-kiefer et al 21 Van de Velde et al 11 and 0.214% (0.165%-0.328%) for ropivacaine, and 0.052% (0.038%-0.064%) and 0.210% (0.164%-0.320%) for levobupivacaine, respectively.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Hoffmann-Kiefer et al . [ 25 ] observed that the mean total consumption was significantly more in ropivacaine group as compared to bupivacaine group.…”
Section: Discussionmentioning
confidence: 99%